IMPLEMENTASI PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PERKULIAHAN CYBER BUSINESS MAHASISWA SISTEM INFORMASI UNIVERSITAS PIGNATELLI TRIPUTRA ANGKATAN 2022 - Rondonuwu, Yeremia Victor (Educational Technology Journal, 2024)
This research aims to evaluate the effectiveness of implementing the Project Base Learning model in CyberBusiness lectures for the Information Systems students of Pignatelli Triputra University, Class of 2022. Theresearch method used is an experiment with a Pretest-Posttest Design. The subjects of the study consist ofone class comprising 18 students. The testing process involved implementing conventional lectures fromthe beginning of the semester until the midterm and then utilizing the project-based learning method untilthe end of the semester. The test results indicate that the data are distributed normally and homogeneous,and the hypothesis testing using the T-test shows that the use of the project-based learning lecture modelsignificantly affects learning outcomes compared to conventional lecture models. This study demonstratesthat the project-based learning model effectively enhances learning outcomes for Information Systemsstudents of Pignatelli Triputra University, Class of 2022, in the Cyber Business course. This lecture orlearning model is an alternative for teachers, educators, and schools to develop more effective, creative,and innovative learning strategies.